The Relationship of Management Elements to the Quality of Outpatient Medical Record Documents at Nashrul Ummah Islamic Hospital Lamongan - Ajeng Putri Mahfiroh; Moch.Fathur Al Mabruri; Dadang Kusbiantoro; Alifin; M. Ganda Saputra; Nihayatul Munaa; Madekhan (Jurnal Surya, 2024)
Introduction: The quality of medical record documents is one of the indicators of the quality of hospital services that can be seen from the completeness of a medical record document.  The purpose of this study is to determine the relationship between management elements and the quality of outpatient medical record documents at Nashrul Ummah Lamongan Islamic Hospital. Methods: The design of this study used correlation analytics with a cross-sectional approach. The sample of this study was 60 respondents using random sampling techniques. The independent variable in this study is the management element, while the dependent variable in this study is the quality of medical record documents. Data was collected using a questionnaire, which included knowledge, SOPs, infrastructure facilities, and a checklist of completeness of medical record documents and observations. The analysis data used the chi-square test with a significance level of p<0.05. Results: The results showed that more than a part (63.9%) of well-informed men had complete medical records, and more than a proportion (79.2%) of poorly knowledgeable men had incomplete medical records. More than a part (69.0%) of those who comply with the SOP have complete medical records, while more than a part (74.2%) of those who do not comply with the SOP have incomplete medical records. More than a part (72.4%) of good infrastructure facilities have complete medical records, while more than a part (77.4%) of poor infrastructure facilities have incomplete medical records. The results of the data analysis stated that there was a relationship between the elements of man, method, and material management to the quality of outpatient medical record documents at the Nashrul Ummah Lamongan Islamic Hospital, with values of p=0.001 and p=0.000 <0.05. Conclusion: It is hoped that the results of this study can be material for improvements in human resources, SOPs, and infrastructure facilities related to medical record documents. Keywords: Health worker, Knowledge, Occupational Health and Safety (K3)